Science Policy for an increasingly diverging Europe (RT. A Journal on Research Policy and Evaluation, 2015)
This paper argues about the need for a revisited public policy framework giving priority to knowledge and technological change across the entire Europe, by discussing new cumulative data on R&D expenditure and the qualification of human resources across Europe. It takes a wide international comparison after a decade hit by recession and economic and budgetary problems, which shows an increasing internal divergence on knowledge investments across Europe, beyond the increasing gap between Europe as a whole and North America. As a result, the paper argues that new paradigms and conditions for responsible science and innovation policy across EU require the collective action of R&D institutions and a system approach to higher education, together with new initiatives towards international cooperation across an enlarged Europe.Analysis shows that chronic backwardness in science and technology in many European peripheries, including in EU southern and eastern regions, have been significantly overcome over the last decade. Nevertheless, their growing scientific and technological capacity is now associated with an increasing vulnerability as a result of the growing international competition for qualified human resources. Additionally, the comparative analysis of levels of economic diversification and sophistication across Europe, suggests the need to insist on qualification and institutional strengthening. This should consider active public policies to attract and retain qualified human resources all over Europe, as well as considering public actions towards promoting new markets. The way in which the economic fabric may gain competitiveness and access to external markets may require enhancing the degree of internationalization of the scientific community and encouraging international knowledge and innovation networks.
Keywords: research policy; education policy